2018
DOI: 10.1007/s13762-018-1652-8
|View full text |Cite
|
Sign up to set email alerts
|

Fate of bromine-containing disinfection by-products precursors during ozone and ultraviolet-based advanced oxidation processes

Abstract: This research evaluates the effect of ultraviolet photolysis, ozonation and ozonation/ultraviolet advanced oxidation processes on different disinfection by-product precursors, during the treatment of water with low organic matter and moderate bromide contents. After different combinations of ultraviolent fluence and ozone, the formation potentials of trihalomethanes and haloacetic acids were investigated. Bromine incorporation factors were used to give specific insight into the behaviour of brominated disinfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In general, the oxidation changes the nature of NOM structures into more hydrophilic compounds, being hydrophobic fractions (humic and fulvic structures) the main responsible for THMs and trihaloacetic acid formation, whereas the more hydrophilic ones are related to dichloroacetic acid generation and the formation of higher concentration of brominated DBPs [75][76][77]. In this line, even with the highest THMs and HAAs formation potential removal by combined O 3 /UV treatment, brominecontaining DBPs present increased toxicity being the conditions between oxidant and UV dose crucial to minimize the risks [78]. Also, the particular characteristics of the NOM play a key role in the suitability of a specific treatment [70,79].…”
Section: Classic Ozonation Processesmentioning
confidence: 99%
“…In general, the oxidation changes the nature of NOM structures into more hydrophilic compounds, being hydrophobic fractions (humic and fulvic structures) the main responsible for THMs and trihaloacetic acid formation, whereas the more hydrophilic ones are related to dichloroacetic acid generation and the formation of higher concentration of brominated DBPs [75][76][77]. In this line, even with the highest THMs and HAAs formation potential removal by combined O 3 /UV treatment, brominecontaining DBPs present increased toxicity being the conditions between oxidant and UV dose crucial to minimize the risks [78]. Also, the particular characteristics of the NOM play a key role in the suitability of a specific treatment [70,79].…”
Section: Classic Ozonation Processesmentioning
confidence: 99%
“…Therefore, UV/O 3 might also produce more AOBr precursors due to its more powerful oxidizing capacity. It has been reported that UV/O 3 has oxidized THM precursors to more hydrophilic substances, which can be easily reacted with bromine . In addition, organic matter transformed by ·OH generated by UV/O 3 process may be more susceptible to halogen incorporation to form AOX …”
Section: Results and Discussionmentioning
confidence: 99%
“…Another potential drawback is the production of toxic disinfection by-products such as oxidised halide species and bromates (which are carcinogenic) may cause pH depression and hamper fish health [2] . Thus, UV radiation [116] and activated carbon filtration [117] may be adopted for pre-treatment, particularly if sea water (usually high in Br) is to be utilised. These pre-treatment methods are also effective for increasing the decomposition rate of residual ozone in the treated water, before feeding back to the main culture tank of the RAQS.…”
Section: Industrial Applications Of Ozonementioning
confidence: 99%